2023
DOI: 10.1002/ajcp.12663
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal patterns and predictors of suicidal ideation in African American adolescents

Abstract: Suicide rates among African American adolescents have increased dramatically. Suicidal ideation is associated with both suicide attempts and completions, thus understanding ideation patterns and predictors in African American adolescents is critical to informing prevention efforts. This study recruited 160 African American ninth grade students. Participants were those students randomized to the control condition of a randomized controlled preventive intervention. Of the 160 participants, 99 completed all asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…African American adolescents report frequent encounters with subtle racial discrimination in their daily lives (Sellers et al, 2006), and such experiences are concurrently and prospectively associated with suicidal ideation, independent of depression symptoms (Madubata et al, 2022). While several studies do suggest that depression symptoms are associated with higher suicidal ideation among African American adolescents (Lambert et al, 2008;Whipple et al, 2023), African American adolescent girls have been shown to report suicidal ideation at lower levels of depressive symptoms, compared to White girls (Robinson, Droege, et al, 2016). In an earlier study, Joe et al (2009) found that only 50% of African American adolescents who have attempted suicide have a diagnosed psychiatric disorder prior to their attempt, suggesting that African American adolescents can be at risk for suicide attempts despite having subclinical mental health symptoms such as depression.…”
Section: Socioecological Stressors and Suicide Risk Inmentioning
confidence: 99%
“…African American adolescents report frequent encounters with subtle racial discrimination in their daily lives (Sellers et al, 2006), and such experiences are concurrently and prospectively associated with suicidal ideation, independent of depression symptoms (Madubata et al, 2022). While several studies do suggest that depression symptoms are associated with higher suicidal ideation among African American adolescents (Lambert et al, 2008;Whipple et al, 2023), African American adolescent girls have been shown to report suicidal ideation at lower levels of depressive symptoms, compared to White girls (Robinson, Droege, et al, 2016). In an earlier study, Joe et al (2009) found that only 50% of African American adolescents who have attempted suicide have a diagnosed psychiatric disorder prior to their attempt, suggesting that African American adolescents can be at risk for suicide attempts despite having subclinical mental health symptoms such as depression.…”
Section: Socioecological Stressors and Suicide Risk Inmentioning
confidence: 99%
“…Far less attention has been devoted to understanding suicide among people of color. Studies that do consider non-White populations often use the catch-all term "other" to represent diverse groups [6,7], or focus exclusively on African Americans and Hispanics [8][9][10][11][12][13], or to a lesser extent American Indians and Alaskan Natives [14,15].…”
Section: Introductionmentioning
confidence: 99%